IoT-Based Innovative Irrigation System for Chili Using Telegram Bot and Web Dashboard - Zulfa Fahrunnisa; Arizal Mujibtamala Nanda Imron; Inta Nurkhaliza Agiska; Wahyu Muldayani; Gamma Aditya Rahardi; Candra Putri Rizkiyah Ramadhani (Politeknik Negeri Batam, 2026)
Chili cultivation requires timely irrigation to maintain soil moisture, yet manual watering is inefficient and difficult to supervise remotely. This paper proposes an IoT-based irrigation system integrating a Telegram bot and a web dashboard for real-time monitoring and control. A soil-moisture sensor provides input to an ESP32 microcontroller, which drives a relay-operated pump using a threshold rule (ON when moisture <30%) and supports manual override via Telegram commands. Sensor readings are logged to Firebase and visualized on a Flask-based dashboard, which features moisture trend graphs. Telegram delivers notifications and supports command-based interaction. Experiments demonstrate an average accuracy of 98,57% and precision of 99,93% compared to a reference meter. End-to-end tests confirm a 0% delivery error, a Telegram notification latency of 1,0–1,8 seconds, and a pump response time of 5,3–5,9 seconds, demonstrating effective automation with practical remote supervision.